The Effect of Self-Ability and Self Confidence on Employee Performance : A Literature Review - Mantha Dabuke, Andre; Veithzal Rivai Zainal; Azis Hakim (Dinasti International Journal of Digital Business Management, 2023)
The aim of this paper is to provide a structured literature review on the constructs of Self-Ability, Self-Confidence, employee performance, and empirical evidence on the relationship between Self-Ability, Self-Confidence, employee performance, in Indonesia context. 30 (thirty) papers published during 2018-2022 that investigates Self-Ability, Self-Confidence, employee performance,, and the relationship between Self-Ability, Self-Confidence, employee performance, were reviewed. The results of the review show that Self-Ability and Self-Confidence From these results, it can be said that each variable instrument, namely Self-Ability and Self-Confidence, affects Employee Performance, but it is undeniable that these variables must run simultaneously and be accompanied by other variables that have not been researched in order to obtain optimal work performance towards better organizational performance.